Abdominal Bruit after Renal Transplantation. Issue 5873 (28th July 1973) - Jachuck, S. J.; Wilkinson, R.
Abstract : Forty-seven recipients of renal allografts have been studied at varying intervals of up to five years after transplantation. Renal artery bruit occurred in eight of 16 patients observed over the first two post-transplant months and disappeared spontaneously in four of these. The disappearance of the bruit was associated with poor renal function. Renal bruits were audible in 10 patients examined more than two months after transplantation; nine of these were hypertensive and of six in whom arteriography was performed five were shown to have stenosis of the allograft artery. By contrast only eight of 37 patients without abdominal bruit were hypertensive, and arteriography in 10 normotensive patients without bruit showed no stenosis. It is concluded that while a renal artery bruit during the first two months after transplantation may be a marker of good renal blood flow at the time, its presence suggests a poor long-term prognosis since persistence of the murmur indicates that significant stenosis of the allograft artery is likely, while its disappearance is associated with poor renal function.